Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Melalui Problem Solving Pada Mata Pelajaran IPA - Kusnawati, Novi (Jurnal Dewantara, 2016)
Method of solving the problem is the method more activity involves students in the learning process in addition to the method of solving the problem is more emphasis on how to stimulate students to think about a problem to be analyzed in an attempt to solve the problem, so that students are able to develop the ability to think critical, especially on learning science. This research is a classroom action research conducted at one of the elementary schools. Based on the study results were measured throughout the study, the learning process in the third cycle has reached KKM set that is equal to 80%. On the condition of prior actions, the students who received grades equal to or greater than the new KKM reached 47%, while, after the achievement of KKM action by 80%. This achievement has been to meet the target of classical KKM expected.